2006
DOI: 10.5194/angeo-24-2075-2006
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical aspects of the onset of Indian summer monsoon from perturbed orography simulations in a GCM

Abstract: Abstract.A theory is proposed to determine the onset of the Indian Summer Monsoon (ISM) in an Atmospheric General Circulation Model (AGCM). The onset of ISM is delayed substantially in the absence of global orography. The impact of orography over different parts of the Earth on the onset of ISM has also been investigated using five additional perturbed simulations. The large difference in the date of onset of ISM in these simulations has been explained by a new theory based on the Surface Moist Static Energy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
70
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 32 publications
14
70
0
Order By: Relevance
“…Observations corroborate such theory [Bordoni and Schneider, 2008;Hurley and Boos, 2013;Nie et al, 2010]. Chakraborty et al [2006], in particular, suggested that the moist static energy just above the surface of India could be used to predict the date of onset of the Indian monsoon.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Observations corroborate such theory [Bordoni and Schneider, 2008;Hurley and Boos, 2013;Nie et al, 2010]. Chakraborty et al [2006], in particular, suggested that the moist static energy just above the surface of India could be used to predict the date of onset of the Indian monsoon.…”
Section: Introductionsupporting
confidence: 61%
“…For MSE, we explored different windows ( Figure S1 in the supporting information) and chose periods that precede the early and late seasons used here by enough that predictions should be possible. The correlation of MSE in the period 1 May to 15 May with All India Rainfall in the period 20 May to 15 June (Figure 1a) shows a large region of positive correlation covering central and north India (including Tibet) and Pakistan, as Chakraborty et al [2006] anticipated. This correlation indicates that heating over this region during the preceding period favors high rainfall during the early season.…”
Section: Predictor Selectionmentioning
confidence: 71%
“…For the late season, correlation coefficients are yet higher, and the band of high correlation extends southwest from Tibet. These correlations suggest a direct relationship between heating of the atmosphere directly above Tibet's surface, and the temperature in the upper troposphere, which many link both to the strength of the monsoon [e.g., Goswami et al, 1999;He et al, 1987He et al, , 2003Li and Yanai, 1996;Wu and Zhang, 1998;Yanai and Wu, 2006;Yanai et al, 1992] and, as Chakraborty et al [2006] suggested, to its onset [e.g., Goswami and Xavier, 2005;Xavier et al, 2007;Webster and Yang, 1992].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies pointed out that the presence of the African plateau was relevant to the Asian monsoon. In numerical experiments by Chakraborty et al [81] the removal of the African topography could delay the onset of the South Asian summer monsoon and weaken its intensity, while once the South Asian summer monsoon was established, the influence of topography on the precipitation intensity was limited. Earlier experiments by Chakraborty et al [75] demonstrated the importance of the African topography in the formation of the Indian monsoon, but the result was that the removal of the African topography led to increased precipitation in the Indian Subcontinent.…”
Section: Contributions Of Other Tectonic Movements To the Establishmementioning
confidence: 99%
“…Not only did the uplifts of southern and northern TP have different climatic and environmental influences, but the effects of the eastern and western topography as well. The numerical experiments of Chakraborty et al [81] discovered that the Asian topography to the west of 80°E had a greater impact than that to the east of 80°E on the onset of the Indian summer monsoon and associated precipitation. The western plateau had a barrier effect on the cold air from high latitudes, favored the atmosphere over south Asia to reach unstable conditions earlier; while the eastern plateau played a minor role in promoting the development of deep convection over the entire Indian region, despite enhancing large-scale ascending air flow in the lower troposphere.…”
Section: Effects Of Himalayan-tibetan Plateau Sub-regional Uplift On mentioning
confidence: 99%